An analysis of intra-extra Asean trade with emphasis on selected commodities - Nepal, Ramesh P.; Tang, John C.S.; Pakorn Adulbhan; Tabucanon, Mario T.; Carl Duisberg Gesellschaft (Bangkok : Asian Institute of Technology, 1979)
The aim of this study is to analyze Intra and Extra-ASEAN trade among the ASEAN member countries, The Association of Southeast Asian Nation was formed by the five countries namely, Indonesia, Malaysia, the Philippines, Singapore and Thailand in 1967. The process of development of the ASEAN region depends on its exports, The bulk of the ASEAN foreign exchange earning at present comes mainly from the export of agricultural products and raw materials to the developed countries, except Singapore, where manufactured goods accounts for most of the foreign exchange earnings, The percentage growth of intra-ASEAN trade as compare to extra-ASEAN trade can be improved. On the extra-ASEAN trade, the traditional trading partners of ASEAN countries are Japan, United States and the EEC, and it has been considered for discussion. ASEAN is facing a lot of problems concerning the exports of its major primary commodities in the international market, This research is carried out to provide a better insight on the problems related to ASEAN trade.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1979
Keywords: Asia, Southeastern -- Commercial policy